The Effect of Tenure Audits, Audit Rotations and Audit Committees on Audit Quality - Ningsih, Wicdia Reka; Alliffiya, Qumaydatun; Rahmawati, Fani (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study will analyze transportation and logistics companies listed on the Indonesia Stock Exchange between 2017 and 2022 to determine the influence of audit tenure, audit rotation, and committee composition on audit quality. Secondary data from this case is the basis for a quantitative approach. 102 data points were collected from 17 sample organizations in the study. This study used statistical tools for panel data analysis, including CEM, FEM, and REM (Random Effect Model). Choosing a suitable panel data regression model is easy with the help of rigorous testing methods such as Chow, Hausman, and LM testing. We then used the F-test, R2 test, and T-test to examine our hypothesis and confirm the relationship was significant. To implement this strategy, we processed the data using EViews version 12, which resulted in meticulous statistical findings. The results show that among the logistics and transportation companies studied, the audit committee does not seem to have a statistically significant influence on audit quality, audit rotation decreases audit quality, and audit duration does not affect audit quality.